SECURITY MEASUREMENT FOR LTE/SAE NETWORK DURING SINGLE RADIO VOICE CALL CONTINUITY (SRVCC). - Jamil, Nazia (My University, 2014)
Voice has significant place in mobile communication networks. Though data applications have extensively gained in importance over the years but voice is still a major source of revenue for mobile operators. It is obvious that voice will remain an important application even in the era of Long Term Evolution (LTE). Basically LTE is an all-IP data-only transport technology using packet switching. Therefore, it introduces challenges to satisfy quality of service expectations for circuit-switched mobile telephony and SMS for LTE capable smartphones, while being served on the LTE network. Since 2013, mobile operators have been busy deploying Voice Over LTE (VoLTE). They are relying on a VoLTE technology called Single Radio Voice Call Continuity (SRVCC) for seamless handover between packet-switch domain to circuit-switch domain or vice versa. The aim of thesis is to review and identify the security measurement during SRVCC and verify test data for ciphering and integrity algorithm.
Keywords: 3GPP; GSMA; LTE/SAE; UMTS; GSM; E-UTRAN; UTRAN; GREAN; CS; PS; Handover; IMS; VoLTE; SRVCC; IRATs; VCC; STN-SR; DTM; PSHO; Kasumi; Snow 3G; ZUC; AES; lu; Integrity and Ciphering algorithms.; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|